La efectiva constitucionalidad de la regulación de derechos estatutarios en la STC 31/2010 - Agudo Zamora, Miguel (Teoría y Realidad Constitucional, 2011)
The possibility that the Statutes of Autonomy regulate rights has been a matter that constitutionalist has turned out to be specially polemic in the last years. The STC 31/2010 concludes this topic proclaiming the effective constitutionality of the regulation of statutory rights and establishing his limited scope. The Constitutional Court has added that the statutory rights are not actually civil rights but simple mandates to the autonomous public power. This supposes that only they will be exigibles when the autonomous legislator has developed them. The statutory rights are materially linked to the own area of the autonomous community.